Factorize this!!

Algebra Level 5

Find sum of all integer values of a a such that the quadratic expression, ( x + a ) ( x + 1991 ) + 1 (x+a)(x+1991)+1 can be factored as a product ( x + b ) ( x + c ) (x + b)(x + c) where b and c are integers.


The answer is 3982.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

5 solutions

Expanding the expression, we have f ( x ) = x 2 + ( 1991 + a ) x + ( 1991 a + 1 ) f(x) = x^{2} + (1991 + a)x + (1991a + 1) .

Now f ( x ) = 0 f(x) = 0 when

x = ( 1991 + a ) ± ( 1991 + a ) 2 4 ( 1991 a + 1 ) 2 = x = \dfrac{-(1991 + a) \pm \sqrt{(1991 + a)^{2} - 4*(1991a + 1)}}{2} =

( 1991 + a ) ± ( 1991 a ) 2 4 2 = \dfrac{-(1991 + a) \pm \sqrt{(1991 - a)^{2} - 4}}{2} =

( 1991 + a ) ± ( ( 1991 a ) + 2 ) ( ( 1991 a ) 2 ) 2 = \dfrac{-(1991 + a) \pm \sqrt{((1991 - a) + 2)((1991 - a) - 2)}}{2} =

( 1991 + a ) ± ( 1993 a ) ( 1989 a ) 2 \dfrac{-(1991 + a) \pm \sqrt{(1993 - a)(1989 - a)}}{2} .

In order to have integer roots, we will require that ( 1993 a ) ( 1989 a ) (1993 - a)(1989 - a) be a perfect square. Now let m = 1989 a m = 1989 - a . Then

( 1993 a ) ( 1989 + a ) = ( m + 4 ) m = ( m 2 + 4 m + 4 ) 4 = ( m + 2 ) 2 4 (1993 - a)(1989 + a) = (m + 4)m = (m^{2} + 4m + 4) - 4 = (m + 2)^{2} - 4 .

Now since the only pair of perfect squares which differ by 4 4 are 0 0 and 4 4 , we must have either m = 0 m = 0 or m + 4 = 0 m + 4 = 0 , i.e., a = 1989 a = 1989 or a = 1993 a = 1993 .

The desired sum is then 1989 + 1993 = 3982 1989 + 1993 = \boxed{3982} .

Comment: Note that in either case we end up with a double root, as the discriminant is zero. With a = 1989 a = 1989 we get b = c = 1990 b = c = 1990 , and with a = 1993 a = 1993 we get b = c = 1992 b = c = 1992 .

Did the same! I think it is an RMO problem, I am not sure but still if it is, you can add it.

Kartik Sharma - 6 years, 6 months ago
Hugh Sir
Nov 22, 2014

Let p ( x ) = ( x + a ) ( x + 1991 ) + 1 = ( x + b ) ( x + c ) p(x) = (x+a)(x+1991)+1 = (x+b)(x+c) .

Then the roots of p ( x ) p(x) are b -b and c -c .

p ( b ) = ( b + a ) ( b + 1991 ) + 1 = 0 p(-b) = (-b+a)(-b+1991)+1 = 0

( a b ) ( 1991 b ) = 1 (a-b)(1991-b) = -1

Since ( a b ) (a-b) and ( 1991 b ) (1991-b) are integers,

and 1 = ( 1 ) ( 1 ) = ( 1 ) ( 1 ) -1 = (-1)(1) = (1)(-1) ;

we can conclude that either a b = 1 a-b = -1 and 1991 b = 1 1991-b = 1 ,

or a b = 1 a-b = 1 and 1991 b = 1 1991-b = -1 .

The first case implies that b = 1990 b = 1990 and a = 1989 a = 1989 .

The second case implies that b = 1992 b = 1992 and a = 1993 a = 1993 .

Therefore, the required sum is 1989 + 1993 = 3982 1989+1993 = 3982 .

Oh, sorry for my duplicate solution. I didn't see you there until I published mine.

Nick Lee - 6 years, 6 months ago

Log in to reply

@Nick Lee It's okay. Yours and mine are not exactly the same, just similar approach. Nicely done, by the way. =)

Hugh Sir - 6 years, 6 months ago

Log in to reply

Thanks! ^^

Nick Lee - 6 years, 6 months ago
Nick Lee
Nov 22, 2014

Expand both of the equations to get x 2 + ( a + 1991 ) x + ( 1991 a + 1 ) = 0 , x 2 + ( b + c ) x + b c = 0 x^{ 2 }+(a+1991)x+(1991a+1)=0,\quad x^2+(b+c)x+bc=0

Since both equations have to be the same... { b + c = a + 1991 1991 b + 1991 c = 1991 a + 199 1 2 b c = 1991 a + 1 \begin{cases} b+c=a+1991\longrightarrow 1991b+1991c=1991a+1991^{ 2 } \\ bc=1991a+1 \end{cases} Subtract the second equation from the first equation to get 1991 b + 1991 c b c = 199 1 2 1 b c 1991 b 1991 c + 199 1 2 = 1 ( b 1991 ) ( c 1991 ) = 1 1991b+1991c-bc=1991^{ 2 }-1\longrightarrow bc-1991b-1991c+1991^{ 2 }=1\\ (b-1991)(c-1991)=1

Because b,c are both integers, this has two solutions.

b 1991 = 1 , c 1991 = 1 b = 1992 , c = 1992 b + c = a + 1991 1992 + 1992 = a + 1991 a = 1993 b-1991=1,\quad c-1991=1\rightarrow b=1992,\quad c=1992\\ b+c=a+1991\longrightarrow 1992+1992=a+1991\\ \therefore a=1993

b 1991 = 1 , c 1991 = 1 b = 1990 , c = 1990 b + c = a + 1991 1990 + 1990 = a + 1991 a = 1989 b-1991=-1,\quad c-1991=-1\rightarrow b=1990,\quad c=1990\\ b+c=a+1991\longrightarrow 1990+1990=a+1991\\ \therefore a=1989

Therefore, the sum of the values of a is 1993+1989=3982

Terrell Bombb
Dec 6, 2016

this is simply completing the square x 2 + ( 1991 + a ) x + 1991 a + 1 x^2 + (1991+a)x + 1991a + 1 since the constant can be completed by dividing the middle term by 2 and then squaring it, we can equate it as such: ( 1991 + a 2 \frac{1991+a}{2} )^2 = 1991a + 1

@Terrell Bombb You need to format the last part. LATEX

Soha Farhin Pine Pine - 4 years, 5 months ago
Alan Yan
Nov 29, 2016

Let f ( x ) = x + b , g ( x ) = x + c f(x) = x+b, g(x) = x+c , so P ( x ) = ( x + a ) ( x + 1991 ) + 1 = ( x + b ) ( x + c ) = f ( x ) g ( x ) P(x) = (x+a)(x+1991) + 1 = (x+b)(x+c) = f(x)g(x) . Observe f ( b ) g ( b ) = 1 f ( c ) g ( c ) = 1 \begin{aligned} f(-b)g(-b) & =1 \\ f(-c)g(-c) &= 1 \end{aligned} Since they are all integer polynomials, we have f ( b ) = g ( b ) , f ( c ) = g ( c ) f(-b) = g(-b), f(-c) = g(-c) . So f ( x ) g ( x ) f(x) - g(x) has 2 roots but degree at most 1. Thus it must be zero, meaning b = c b = c .

We have ( x + b ) 2 = ( x + a ) ( x + 1991 ) + 1 ( x + b 1 ) ( x + b + 1 ) = ( x + a ) ( x + 1991 ) . (x+b)^2 = (x+a)(x+1991) +1 \implies (x + b-1)(x + b + 1) = (x+a)(x+1991). Matching the roots gives us a = 1989 , 1993 a = 1989, 1993 .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...